2021
DOI: 10.1158/0008-5472.can-20-1293
|View full text |Cite
|
Sign up to set email alerts
|

Secretory Mucin 5AC Promotes Neoplastic Progression by Augmenting KLF4-Mediated Pancreatic Cancer Cell Stemness

Abstract: Secreted mucin 5AC (MUC5AC) is the most abundantly overexpressed member of the mucin family during early pancreatic intraepithelial neoplasia stage I (PanIN-I) of pancreatic cancer. To comprehend the contribution of Muc5ac in pancreatic cancer pathology, we genetically ablated it in an autochthonous murine model (KrasG12D; Pdx-1cre, KC), which mirrors the early stages of pancreatic cancer development. Neoplastic onset and the PanIN lesion progression were significantly delayed in Muc5ac knockout (KrasG12D; Pdx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 39 publications
0
37
0
Order By: Relevance
“…Paradoxically, MUC2 has increased expression level in certain types of gastrointestinal malignancies 21,27 , which denotes that MUC2 may also be employed by cancer cells and function as mucous barrier against anti-tumour immune reaction. MUC5 is another secreted mucin and promotes KLF4 mediated PDAC cancerous stemness 9 . In addition, CA19-9, the most commonly used prognostic marker for pancreatic cancerous disease, is present on the surface of MUC1 and MUC5 20,28 ; With respect to the recent discovery that CA19-9 bolsters PDAC initiation and progression 29 , the interaction between mucins and CA19-9 suggests that mucins are not merely prognostic factors but also participate in the onset and advancement of PDAC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Paradoxically, MUC2 has increased expression level in certain types of gastrointestinal malignancies 21,27 , which denotes that MUC2 may also be employed by cancer cells and function as mucous barrier against anti-tumour immune reaction. MUC5 is another secreted mucin and promotes KLF4 mediated PDAC cancerous stemness 9 . In addition, CA19-9, the most commonly used prognostic marker for pancreatic cancerous disease, is present on the surface of MUC1 and MUC5 20,28 ; With respect to the recent discovery that CA19-9 bolsters PDAC initiation and progression 29 , the interaction between mucins and CA19-9 suggests that mucins are not merely prognostic factors but also participate in the onset and advancement of PDAC.…”
Section: Discussionmentioning
confidence: 99%
“…MUC2 is secreted to form insoluble mucous gel barrier and generally identi ed as a tumour suppressor 8 , both normal pancreatic tissue and PDAC rarely have a positive expression of MUC2. Another gel forming mucin MUC5, on the contrary, is abundantly overexpressed in PDAC tissues and potentiates oncogenic signalling pathway 9 . Correspondingly, these aberrantly glycosylated mucins can be recognized as tumour associated antigens, which could be employed as useful predictors for the effectiveness of adjuvant therapy 10,11 and potential targets for cancer therapy 12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, GALNT-6 elevated mucin-O-glycosylation of a2M, which activates downstream PI3/Akt signaling pathway, fosters metastasis of breast cancer (69). CD44+, CD24+ and CD133+ CSC populations of pancreatic cancer also express Mucin-1 (115) and Mucin 5AC also plays significant role in maintaining stemness properties of pancreatic CSC (116). Increased fraction of CD44+, CD24-CSC and Mucin-1 expression was also reported in breast cancer MCF-7 cells when exposed to tumor associated macrophages (117).…”
Section: Glycosylation Of Csc Markersmentioning
confidence: 99%
“…Increasing evidences have suggested that all the three subgroups' MUC members are closely linked to cancer initiation and progression. For example, Ganguly et al found that secretory MUC5AC promoted neoplastic progression by augmenting KLF4-mediated pancreatic cancer cell stemness [7]; Xu et al indicated that MUC1 was overexpressed in NSCLC and silence of MUC1 alleviated paclitaxel resistance of NSCLC [8]; Gao et al suggested that MUC12 enhanced RCC progression by regulating c-Jun/TGF-β signaling [9]; Tiemin et al found that MUC13 facilitated progression of intrahepatic cholangiocarcinoma via EGFR/PI3K/AKT pathways [10]. Moreover, dysregulated MUCs are reported to serve as potential biomarkers in multiple tumor types.…”
Section: Introductionmentioning
confidence: 99%